2019
DOI: 10.34301/alsc.v2i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive Analysis of English and Albanian Adjectives

Abstract: Language is a systematic means of communicating by the use of sounds or conventional symbols. Learning a foreign language is never easy especially when we try to express our thought, opinions, feelings and ideas from mother language to target language. Because English is so widely spoken, it has often been referred to as a “world language” or “lingua franca’. While it is not an official language in most countries, it is currently the language most often taught as a foreign language. Since English language is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…This shows that translation strategy was a norm for the students. The study conducted by (Spahiu, 2013) also found that some translated words especially the language of the students' mother tongue were found to have helped the students to learn English better. Apparently, the guidance provided to the students would fall into the categories of controlled and guided writing which showed that the participants had opted for the strategies of the Product Approach where the end-product was focused by providing ample of guidance.…”
Section: P9mentioning
confidence: 93%
“…This shows that translation strategy was a norm for the students. The study conducted by (Spahiu, 2013) also found that some translated words especially the language of the students' mother tongue were found to have helped the students to learn English better. Apparently, the guidance provided to the students would fall into the categories of controlled and guided writing which showed that the participants had opted for the strategies of the Product Approach where the end-product was focused by providing ample of guidance.…”
Section: P9mentioning
confidence: 93%
“…The interrogative form of a sentence, for example, was misinterpreted as a statement due to the incorrect arrangement of the subject and auxiliary verb. The reasons of Albanian ESL students' selection errors, omission errors, addition errors, and syntax problems were discovered (Spahiu & Spahiu, 2019;Spahiu et al, 2021;Swan, 1997).…”
Section: Conclusion and Commentsmentioning
confidence: 99%